The Use of Social Media in Islamic Religious Education Learning and Its Implications for Student Character - Marlina, Marlina; Nadirah, Sitti (PT. Anagata Sembagi Education, 2024)
This study aims to explore the impact of social media use in Islamic religious education learning on student motivation and engagement. The method used is qualitative analysis by collecting data through surveys and in-depth interviews with students who engage in religious learning using social media platforms. The results of the analysis showed that social media significantly increased students' motivation, with many of them reporting a higher sense of passion for learning when interacting with friends and teachers through these platforms. The interactions that occur on social media create a fun and dynamic learning atmosphere, which increases students' interest in learning religious materials. With the opportunity to discuss and exchange ideas, students feel more involved in the learning process, which in turn strengthens their understanding of Islamic values. The findings indicate that the integration of social media in the religious education curriculum can be an effective strategy to increase student engagement and support more interactive learning in the digital age.